Relationship between dietary protein intake and prevalence of sarcopenia in older adults - Yu, Duoduo; Liu, Buyun; Wang, Biao; Wang, Mei (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the relationship between sarcopenia and dietary protein use among adults. Method: The retrospective, cross-sectional study was conducted after approval from the ethics review committee of Sichuan Province Orthopaedic Hospital, China, and comprised prospective data of American adults aged at least 20 years who had participated in the National Health and Nutrition Examination Survey between 2015 and 2018. The survey had complete information on protein intake and sarcopenia status. It was analysed from June to September 2023, and was made public in September 2023. Baseline characteristics were examined, and confounding factors were determined. Data was analysed using R software version 4.2.2. Results: Of the 5,222 participants with mean age 39.9±11.5 years, 2,708(51.9%) were females and 2.514(48.1%) were males. Sarcopenia was diagnosed in 524(10%) subjects. Those with dietary protein intake less-than56.7g/day had higher odds of sarcopenia compared to the rest (p less-than 0.05). Conclusion: Consuming enough protein in the diet may help shield adults from developing sarcopenia. Key Words: Dietary proteins, Skeletal, Elderly, Cross-sectional studies, Correlation.